Modeling the Lion Attack in Cognitive Radio Networks. (3rd August 2010) - Hernandez-Serrano, Juan; León, Olga; Soriano, Miguel
Abstract : Cognitive radio is a promising technology aiming to improve the utilization of the radio electromagnetic spectrum. A cognitive radio is a smart device which runs radio applications software to perform signal processing. The use of this software enables the device to sense and understand its environment and actively change its mode of operation based on its observations. Unfortunately, this solution entails new security challenges. In this paper, we present a cross-layer attack to TCP connections in cognitive radio networks, analyze its impact on TCP throughput via analytical model and simulation, and propose potential countermeasures to mitigate it.